Correlation analysis of the life time of coolant used in CNC machines and productivity in the metallic industry of Mexicali - Mildrend Ivett Montoya-Reyes; Juan Ceballos-Corral; Ismael Mendoza-Muñoz; Olivia Yessenia Vargas-Bernal (Revista de Ciencias Tecnológicas, 2022)
The use of taladrina in cutting processes in the metallic industry of Mexicali is of great relevance due to its functionality of reducing friction between cutting metals (cutting material to be processed and cutting tool). This manufacturing process is generated in a metallic material that an optimal finish of a metallic surface is obtained and helps to a great extent to extend the life of the tools of the CNC cutting machine. In this research, three phases were considered in its development, being the first stage, a detailed evaluation of the use of taladrina (daily, weekly, monthly, seasonally and yearly), utilized in a cutting process of a CNC machine of a metallic industry located in the city of Mexicali. In this phase, a considerable use of coolant was observed, of up to 40% more, causing a great concern of the managerial, administrative and supervisory personnel for a 25% of extra expenses of economic expenses; whose objective of this investigation was to reduce both the use of coolant and economic expenses. The second stage was an analysis of the physicochemical properties of taladrina (viscosity and pH)), in periods of every eight hours and compared with the manufacturer's specifications to determine its optimal functionality in the cutting process. The physicochemical analyzes showed that the coolant with an efficient recovery process could be reused, achieving up to 80% recovery with the process proposed in this research, for its reuse with optimal functioning, to achieve savings in the use of coolant. and economic expenses. The third stage was a simulation analysis with the MatLab software with the use of the Simulink process and the PID algorithm (P-Proportional, I-Integral, D-Derivative), to determine the optimal physicochemical characteristics of taladrina, evaluating its viscosity, pH and temperature in daily periods. This phase was relevant to determine in the future the appropriate use of coolant with the recovery process and achieve the savings proposed in the objectives at the beginning of this scientific study. The investigation was developed from 2019 to 2020.